Asymmetric Synthesis of the 9-Azabicyclo[3.3.1]nonane Core of Macroline-Type Alkaloids - Bohn, Ashlyn G.; Cipriano, Benjamin M.; Tasker, Nikhil R.; Wipf, Peter (Synthesis, 2026)
The signature indole-fused 9-azabicyclo[3.3.1]nonane (9-ABN) core of macroline-type alkaloids in its natural configuration has been accessed in 4 steps and 16% overall yield from 1H-indole and an l-menthyl nicotinate-derived pyridyl alcohol. The two starting fragments were condensed using a hydrogen auto-transfer (HA) strategy. The key stereocenter at C-5 was installed in up to 95:5 dr with a double diastereoselective, chiral auxiliary-assisted asymmetric transfer hydrogenation (CAATHy). This selective partial reduction of the pyridine to the tetrahydropyridine set the stage for stereospecific formation of the bridged, bicyclic 9-ABN system via a novel superacid-mediated cycloisomerization reaction. Starting from indole and 6-(hydroxymethyl)nicotinate esters, this new strategy provides rapid, protecting group- and transition metal-free access to the tetracyclic macroline core.
Keywords: Macroline; Alkaloids; 9-Azabicyclo[3.3.1]nonane; Hydrogen auto-transfer; Asymmetric transfer hydrogenation; Partial pyridine reduction